Monitoring Penggunaan Daya Listrik menggunakan Protokol MQTT berbasis Web - Rifqi Zumadilla Pratama; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Current technological developments, especially in the IT field have been developing very rapidly. Now, by using the internet, we can do anything even though we are far apart. One technology that utilizes the internet is a monitoring system or commonly called the Internet of Things. At present, the number of users of electricity is increasing from year to year. One of the services currently available is postpaid electricity service. However, in the distribution of electricity usage data is still done conventionally and data retrieval is done in an uncertain time span. From these problems, data collection and transmission can be carried out in a more efficient way by monitoring electricity usage in realtime on a publish-subscribe-based MQTT protocol. The monitoring system that is run has a small delay, which is 11 ms. In addition, the MQTT protocol can also be run on limited network conditions, namely on network conditions that have low bandwidth. At 32KBps the average delay is 17 ms. So the system can be run on a limited network.